IMPLEMENTATION OF BUSINESS INTELLIGENCE TO ANALYZE DISTRIBUTION OF COVID-19 CASES IN INDONESIA - Hifzon, Hifzon; Ashari, Muhamad Ihsan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2023)
Abstract: Covid-19 cases started showing up in Indonesia in early March 2020, and they have since spread to several other areas. The number of corona virus infections from different Indonesian provinces plays a significant role in the decision-making process based on this data visualization. By creating a Business Intelligence system to display the results of the number of confirmed cases, deaths, and recoveries from various provinces in Indonesia, the goal of this project is to visualize data on corona virus cases. The Corona Virus Dataset in Indonesia from www.kaggle.com is processed using Grafana in this article. The findings of this article are presented as dashboard reports that include data on confirmed cases, fatalities, and recoveries in different Indonesian provinces. These reports can be utilized to help make decisions. With Grafana's interactive dashboard features, the data display resulting from routine analysis results can be engaging. Keywords: Business Intelligence, OLAP, Covid 19 Abstrak: Kasus Covid-19 mulai muncul di Indonesia pada awal Maret 2020, dan sejak itu menyebar ke beberapa daerah lain. Keputusan berdasarkan visualisasi data sering kali mencakup statistik jumlah kasus virus corona dari berbagai provinsi di Indonesia. Dengan membuat sistem Business Intelligence untuk menampilkan temuan jumlah kasus terkonfirmasi, kematian, dan pemulihan dari berbagai provinsi di Indonesia, tujuan penelitian ini adalah untuk memvisualisasikan data kasus virus corona. Postingan ini menggunakan Grafana untuk menangani dataset virus corona Indonesia dari www.kaggle.com. Temuan artikel ini disajikan sebagai laporan dalam bentuk dasbor yang mencakup data jumlah kasus terkonfirmasi, kematian, dan pemulihan di berbagai provinsi di Indonesia. Dengan pengaturan dashboard interaktif Grafana, mungkin akan menarik untuk melihat data yang dihasilkan dari hasil analisis standar yang ditampilkan. Kata kunci: Business Intelligence, OLAP, Covid 19